Dormitorietrappen i Sorø Klosterkirke - og i andre danske munkeklostre - Vedsø, Mogens (Hikuin, 2012)
The Dormitory Stairs in Sorø Abbey Church By Mogens Vedsø The dormitory stairs in the medieval Danish monasteries that attract the most attention are the stairs in Sorø Abbey Church in the south transept. On the one hand they are regarded as a prototype of such stairs, on the other they are considered well preserved and safely dated. These statements call for further examination. The staircase has two flights along the west wall and south gable of the transept leading up to a landing in front of the door to the dormitory about 3.5 m above the floor. The staircase has one thick stone parapet and at its free northeastern corner has a brick column with an almost egg-shaped ball on top. The stairs seem well preserved, but the construction of chapels associated with the two barrel vaults of the upper flights may have caused some changes?. The Danish art historian N.L. Høyen concluded in his description of the church from 1869 that the original design of the stairs was uncertain. The current design is therefore partly due to the church restorations carried out after the middle of the 19th century. The dating of the staircase has long been closely associated with the fire in the church and the convent in 1241. Before construction of the east wing, of which some remains are still preserved, there was a significantly lower wing linked to the southern transept. Access to its upper story was through a door that was somewhat lower than its successor and therefore was supposedly not used with the younger monastery wing. The staircase should therefore be of the same age as the former door. The wing is generally dated to the time after the fire, but the shape of its vaults suggests that it may be older. However, the observations in the vaults of the vestry and the adjacent library – to the west – show that the older staircase could have been used even after the construction of the new east wing. The staircase dating can therefore be linked neither to the construction of the east wing nor to the monastery fire of 1241 Details of the staircase itself suggest a dating to the mid-13th century. It remains to consider whether the staircase design is consistent with the general picture of similar steps in other abbeys. The large Cistercian abbey churches in Herrevad and Løgum had related stairs (respectively from the second half of the 12th century and from the mid-13th century). No example of a staircase designed like the old staircase in Sorø is known in Denmark, but similar remains are known from the Swedish Cistercian abbey church in Alvastra (consecrated around 1185). Stairs from the 14th and 15th century, which once ascended from the chancel floor, are known for example from Elsinore St. Mary, Holbæk and Faaborg. From the later part of the Middle Ages a new type is known, where the stairs are located in the east wing of the monastery in close proximity to the church. Such stairs are known for example from Kalundborg, Odense St. Knud and Nykøbing Falster. Another type is the stairs that were reached via a connecting room. Examples include Aalborg and Ystad. Further examples of dormitory stairs may have been built, but those cited here already show a clear trend. First of all, it must be concluded that the stairs in Sorø, if not an isolated occurrence, were at least a rarity. Most of the previous types of stairs are far more unostentatious. The old stairs in general seem, at least in the case of the stair flight, to have been placed inside the church. On the other hand, most of the younger medieval stairs have been removed from the church and instead placed in or adjacent to the east wing. The purpose of this article has been to provide an overview; for most stairs we still lack a closer examination of the exact construction and dating in the sources. The core of this review indicates that the picture is somewhat more complex than expected, and future studies will undoubtedly make it more nuanced.